A note on matching covered graphs - Vahan V. Mkrtchyan (Изд-во НАН РА)
A graph is called matching covered if for its every edge there is a maximum matching containing it. It is shown that line-extremal matching covered graphs contain a perfect matching.
Keywords: Mathematics; Graph theory